Cyclization of propargylic amides: mild access to oxazole derivatives - Weyrauch, Jan P.; Hashmi, A. Stephen K.; Schuster, Andreas M.; Hengst, Tobias; Schetter, Stefanie; Littmann, Anna Christina; Rudolph, Matthias; Hamzić, Melissa; Visus, Jorge; Rominger, Frank; Frey, Wolfgang; Bats, Jan W. (Chemistry - a European journal, 2010)
The substrate scope, the mechanistic aspects of the gold-catalyzed oxazole synthesis, and substrates with different aliphatic, aromatic, and functional groups in the side chain were investigated. Even molecules with several propargyl amide groups could easily be converted, delivering di- and trioxazoles with interesting optical properties. Furthermore, the scope of the gold(I)-catalyzed alkylidene synthesis was investigated. Further functionalizations of these isolable intermediates of the oxazole synthesis were developed and chelate ligands can be obtained. The use of Barluenga’s reagent offers a new and mild access to the synthetically valuable iodoalkylideneoxazoles from propargylic amides, this reagent being superior to other sources of halogens.
First published: 14 January 2010
Gesehen am 29.11.2023